Dementia and patient outcomes after hip surgery in older patients: A retrospective observational study using nationwide administrative data in Japan. - Noriko Morioka; Mutsuko Moriwaki; Jun Tomio; Kiyohide Fushimi; Yasuko Ogata (PLoS ONE)
Objective To investigate whether dementia is associated with incidence of adverse events and longer hospital stays in older adults who underwent hip surgery, after adjusting for individual social and nursing care environment. Design and setting Retrospective observational study using the linked data between the Japanese Diagnosis Procedure Combination database and the reports of the medical functions of hospital beds database in Japan (April 2016-March 2017). Participants A total of 48,797 individuals aged 65 and older who underwent hip surgery and were discharged during the study period. Methods Outcomes included in-hospital death, in-hospital pneumonia, in-hospital fracture, and longer hospital stay. We performed two-level, multilevel models adjusting for individual and hospital characteristics. Results Among all participants, 20,638 individuals (42.3%) had dementia. The incidence of adverse events for those with and without dementia included in-hospital death: 2.11% and 1.11%, in-hospital pneumonia: 0.15% and 0.07%, and in-hospital fracture: 3.76% and 3.05%, respectively. The median (inter quartile range) length of hospital stay for those with and without dementia were 26 (19-39) and 25 (19-37) days, respectively. Overall, the odds ratios (95% confidence interval (CI)) of dementia for in-hospital death, in-hospital pneumonia, and in-hospital fracture were 1.12 (0.95-1.33), 0.95 (0.51-1.80), and 1.08 (0.92-1.25), respectively. Dementia was not associated with the length of hospital stay (% change) (-0.7%, 95% CI -1.6-0.3%). Admission from home, discharge to home, and lower nurse staffing were associated with prolonged hospital stays. Conclusions Although adverse events are more likely to occur in older adults with dementia than in those without dementia after hip surgery, we found no evidence of an association between dementia and adverse events or the length of hospital stay after adjusting for individual social and nursing care environment.